Boarding School as A Model for Character Education Development to Realize the Profile of Pancasila Students - I Wayan Gustama; Sukadi; Ida Bagus Made Astawa (ASANKA : Journal of Social Science and Education, 2025)
This study aims to analyze the character education model implemented at the boarding school SMAN Bali Mandara and its implications for the Pancasila Student Profile. The background of this research is based on the change in status of SMAN Bali Mandara from a boarding school to a regular school in the 2022/2023 academic year and its impact on student character. This study uses a qualitative approach with a case study method. Data were collected through interviews, observations, documentation, and questionnaires directed at the principal, teachers, dormitory head, and students. The results of the study show that boarding schools have advantages in shaping student character through a holistic education program, including intracurricular activities, extracurricular activities, Pancasila Student Profile strengthening projects, and school culture. This research concludes that boarding schools can be an effective model in the development of character education to realize the Pancasila Student Profile.